EKSPLORASI ETNOMATEMATIKA RITUAL SEBLANG OLEHSARI TERHADAP KONSEP GEOMETRI - Rahmani, Putri Aprilia Eka; Susanto, S; Monalisa, Lioni Anka; Hobri, H; Murtikusuma, Randi Pratama (Department of Mathematics Education , University of Jember, 2018)
Abstract. The purpose of this research to describe the ethnomatematics of the Seblang Olehsari Ritual on the concept of geometry. The research method is descriptive qualitative research using ethnography. The Subject of this study is pawang and dancer of Seblang Olehsari. Data collection with survey, observation and intervews. The results showed that ethnomatematics was used by the Osing ethnic in carrying out the Seblang Olehsari ritual, such as: in the design of ritual places, designing dance costumes and dance patterns performed by dancers when trance. The mathematical concept (geometry) that applied by Osing ethnic, include: the concepts of points, lines, angles, flat shapes, similarity, congruent, and geometric transformations Keywords: Ethnomatematics, Seblang Olehsari Ritual, Geometry.